THE MEANING OF JAVANESE TRADITION TEMU MANTEN IN DESA BRUMBUNGAN KIDUL KECAMATAN MARON KABUPATEN PROBOLINGGO - Mohammad Zamroni; Avon Yosi Hartono (JURNAL LITERASI, 2023)
The purpose of this study is to describe in depth the meaning and reveal the cultural values contained in the Temu Manten ceremony in Brumbungan Kidul Village. Many people are actors in the Temu Manten ceremony but do not know the meaning contained in each series of these ceremonies. This study uses the Symbolic Interactionalism Theory by George Herbert Mead, which is a research that examines social and cultural groups in society in depth. So that researchers must be involved and directly follow the daily aspects of their research. This study uses a qualitative method that aims to describe the symbolic meaning of Temu Manten in Brumbungan Kidul Village. In Brumbungan Kidul Village, only people who have more money use Complete Javanese Traditional Weddings. For the lower middle class, they usually only use yellow rice cone which is eaten with their lover after the marriage contract. The Temu Manten tradition is a package with displays and MUA or called WO (Wedding Organizer). It can be concluded that marriage with the Temu Manten tradition can be said to be a marker of social status.